Analisis Risiko Pasar DOC dan Pakan serta Harga Broiler terhadap Pertumbuhan Pengusaha Kecil Peternakan Ayam Broiler di Indonesia - Ezra, Mohammad; Roessali, Wiludjeng; Setiadi, Agus (Universitas Galuh, 2025)
ABSTRACT The purpose of this study is to analyze the risk of DOC (X1), feed (X2) and broiler (X3) prices and their influence on the growth of small broiler chicken farms in Indonesia (Y). This study was conducted by taking data on DOC, feed and broiler prices for the period 2017-2024 (Pre-COVID19, Post-COVID19 and Present) as well as broiler chicken population data nationally in Indonesia from the 2017-2022 range as a dependent variable approach, namely the number of active livestock in Indonesia and trend projection of the number of livestock in 2023 and 2024. The research method used was secondary data research using data from the website of the Directorate General of PKH (Livestock and Animal Health) of the Ministry of Agriculture, SIMPONI-Ternak, and BPS. The data analysis method used in this study uses Standard Deviation (SD), Coefficient of Variance (CV), trend projection and multiple linear regression analysis to see how large the affect of independent variable towards dependent variable. The dependent variable data processing approach uses the number of broiler chicken populations in Indonesia based on BPS data, assuming based on the Livestock Household Survey (2014) that per livestock business household business in Indonesia with livestock control of 16.000 broiler chicken populations. The results of the risk calculation obtained the result of feed prices having the highest coefficient of variance with a value of 21.94% in the current period. Meanwhile, the results of multiple linear regression obtained results only in 2017-2019 (Pre-COVID19) where feed variables affected the growth of small broiler chicken farm entrepreneurs in Indonesia, while in the Post-COVID19 and Present period, DOC price variables, feed prices and selling prices did not affect the growth of broiler chicken farm small entrepreneurs in Indonesia. As well as the projection trend of the number of active livestock in 2023 and 2024 is increasing.